Analisis faktor – faktor yanng mempengaruhi minat kunjungan ulang wisatawan ke Kebun Binatang Taman Rimba Provinsi Jambi - Mesi Fitriani; Syaparuddin Syaparuddin; Jaya Kusuma Edy (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2021)
The purpose of this study was conducted to determine (1) the development of tourists to the Taman Rimba zoo in Jambi Province (2) to analyze the factors that influence tourist attraction, facilities, accessibility, and service quality on the interest in visiting tourists' return visits. Methods of data collection through observation and distribution of questionnaires to respondents. The data source used is primary data obtained directly from the distribution of questionnaires as many as 157 with 5 question items each. The software used in this research examiner is Statistical Package for The Social Sciences (SPSS). The results of the analysis of this study indicate that simultaneously or together the attractiveness and facilities have a significant or positive effect on the interest in visiting tourists' return visits. Meanwhile, accessibility and service quality has a negative effect on the interest in returning tourists. Partially the average attractiveness, facilities, accessibility, and service quality have a positive or significant effect on the interest in revisiting tourists. Keywords: Tourist attraction, Facilities, Accessibility, Service quality, Interest of return tourists.